The Effect of Endurance Training with MAF Concept on VO₂Max Improvement in Male 1500-Meter Runners at Tiger Athletics Club, Bahorok (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to determine the effect of endurance training using the Maximum Aerobic Function (MAF) concept on the VO₂Max improvement of male 1500-meter runners at the Tiger Athletics Club Bahorok. The research method used was an experimental one-group pretest-posttest design involving eight athletes selected through purposive sampling. The training consisted of endurance-based activities (uphill, downhill, and cross-country runs) over six weeks, with three sessions per week. VO₂Max was measured using the Bleep test before and after the training. The data analysis employed a paired t-test, with results showing a significant difference in VO₂Max values pre- and post-training (t = 5.6568 > t₀.₀₅(7) = 1.8946), indicating that the training had a significant effect. Although the improvement percentages varied among athletes, all were classified within the “low” category according to the normalised gain score. The findings suggest that the MAF-based endurance training program can improve VO₂ Max in middle-distance runners and can be applied as an effective alternative for developing aerobic capacity in athletes.